Prospective physics teachers’ specialized content knowledge in Newtonian mechanics - Peşman, Haki (Sakarya University, 2016)
What knowledge teachers must hold to be an effective teacher has been particularly investigated for several decades. A first systematic attempt to define teacher knowledge was made by Shulman and his colleagues. Pedagogical knowledge (PK), subject matter knowledge (SMK) and pedagogical content knowledge (PCK) were three main components of their model explaining what knowledge a science teacher must have. However, Ball, Thames, and Phelps (2008) reported some criticism particularly about SMK in that model. In this new perspective, SMK of science teachers is redefined through Common Content Knowledge (CCK), Specialized Content Knowledge (SCK), and Horizon Content Knowledge (HCK). CCK is related to the knowledge and skills which are utilized in other settings as well as teaching. SCK is related to the knowledge and skills which are special to teaching rather than other settings. Finally, what degree a teacher is aware of the relation of a content knowledge to a future content knowledge in the curriculum is defined as the HCK. In this study, an open-ended questionnaire on Newtonian mechanics was administered to 39 prospective physics teachers participating in the Pedagogical Formation Education at Fırat University. That is, the research is a cross-sectional survey study. In the questionnaire, there were three questions about motion in non-inertial frames. The physics teacher candidates were required to draw the free-body diagrams and use the Newton’s laws. Because Newton’s laws can only be used in inertial frames, they needed to select an inertial frame on the problem solutions. However, they mostly tried to use Newton’s laws in non-inertial frames, and thus, could not properly draw the desired free body diagrams either. Indeed, they had to use some imaginary forces such as centrifugal and inertial forces. However, the use of such unrealistic forces is a sign of misconceptions in physics and physics teachers must not suggest their students to use such forces. Sometimes students may suggest different approaches to problems which are unfamiliar to the teacher. In this case, the teacher must be able to decide if the approach is correct or incorrect and if it can be used for all other similar problems if it is correct. This type of teacher knowledge is associated with SCK. As a result, physics teacher candidates in this study were observed to use undesired approaches to solve physics problems in non-inertial frames which even their students must not be encouraged to use. In conclusion, candidate physics teachers seem not to have a desired level of SCK in Newtonian physics. © The Turkish Online Journal of Educational Technology.